Dietary antioxidant intake increases ankle brachial pressure index in men but not in women: a cross-sectional study - Wang, Yuting; Wang, Jianfeng (Frontiers in Cardiovascular Medicine, 2024)
Objective Atherosclerosis is a significant cause of cardiovascular and cerebrovascular diseases, with a greater impact on men than women. Dietary antioxidant intake is inversely related to the risk of atherosclerosis development. We aimed to investigate the association between dietary composite antioxidant intake and the ankle brachial pressure index (ABPI). The ABPI is not only used for assessing the progression of arterial lesions but also for stratifying the risk of atherosclerotic disease. Methods We conducted a cross-sectional analysis involving 1,049 participants from the National Health and Nutrition Examination Survey (NHANES). We examined six antioxidants (zinc, selenium, carotenoids, and vitamins A, C, and E) and a composite dietary antioxidant index (CDAI) derived from these antioxidants as exposure variables. The primary outcomes encompassed cardio-metabolic parameters, including body mass index (BMI), body fat mass (BFM), systolic and diastolic blood pressure, triglycerides, HDL and LDL cholesterol, C-reactive protein, and the Ankle-Brachial Pressure Index (ABPI). Associations and interactions between variables were assessed using linear regression analyses. Moreover, mediation and moderation analysis is employed. Results Hierarchical multiple regression analysis revealed that among men, dietary intake of zinc, selenium, and vitamin A remained positively associated with a higher ABPI even after adjusting for covariates. Conversely, in the stratified regression analysis based on CDAI quartiles, a U-shaped association between CDAI and ABPI was suggested. Notably, no significant association between dietary antioxidant intake and ABPI was observed among women. CDAI, intake of Vitamin A, Vitamin C, and Vitamin E do not influence all-cause death through mediation by abpi, but rather have a direct effect on all-cause death. Moreover, there is a significant interaction between the intake of Vitamin A and gender, where a daily intake of Vitamin A more than 776 ug is especially beneficial for women. Conclusion The combined intake of nutrients with antioxidant properties may prevent the initiation and progression of atherosclerosis and influence the outcome in a sex-specific manner.